Compensation to retrenched worker: with reference to Malaysian law and Syariah (Islamic Law) - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (International Organisation Centre of Academic Research, 2014)
An employer, where possible, should not retrench his workers because this would place the worker in idleness and unemployment, which in turn would lead to social hazards and could cause stability of society and the economy of the country. Equally, an employer has the right to improve the viability or the efficiency of their business by rationalisation and reorganisation of their association. Unless the employee could be redeployed in some other capacity in the organisation, this would require laying-off or making workers redundant. Where retrenchment is unavoidable, this brings us to the payment of retrenchment compensation. Generally, the law in Malaysia does not make it obligatory on the employer to pay retrenchment compensation to a person who has been retrenched. Hence, this paper will discuss the law and practice in Malaysia on the payment of retrenchment compensation and compare it with the Syariah or Islamic law where the issue considered would be whether in Islam the unemployed has the right to claim from public treasury of the Muslim State and if so, the requirements that need to be satisfied as contained in the Qur'an. In fact, Islam calls out to work, encourages more efforts to produce wealth and forbids idleness and unemployment. Further, Islam also encourages the maximum payment of benefits to workers so as to secure the even distribution of profits. It must be emphasised that the Syari'ah(Islamic law) does not lack in guiding principles in view of its wide coverage of injunctions in respect of labour welfare. The authors will submit that retrenchment is something that is abhorred in Islam because it causes a person to lose his job and being without a job or being unemployed is against the vein of the Qur'an. If circumstances are pressing, then the State must come in to provide another job for the retrenched worker instead of allowing him to be idle. This was also the practise of the Prophet (SAW). For those who are jobless due to the fact that they have been retrenched and there is no job available for them, then zakat has to be resorted to temporarily to help the really needy workers.